Cascade reactions of aryl-substituted terminal alkynes involving in situ-generated α-imino gold carbenes - Sun, Qiaoying; Hüßler, Christopher; Kahle, Justin; Mackenroth, Alexandra; Rudolph, Matthias; Krämer, Petra; Oeser, Thomas; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2024)
An efficient, highly selective and divergent synthetic method to construct 2-substituted indoles and aryl-annulated carbazoles via the intermolecular generation of α-imino gold carbenes from terminal alkynes or diynes in combination with sulfilimines is disclosed. Importantly, the tandem reaction is proposed to proceed through an intermolecular gold carbene generation/C−H annulation followed by the activation of a second alkyne leading to 6-endo-dig cyclization, which is significantly different from previous dual activation or 1,6-carbene shift approaches for diyne systems. In the case of ortho-alkynylaniline as starting material, an unexpected regioselective formation of the indole moiety via the intermolecular path, instead of intramolecular hydroamination was discovered. This reactivity paved the way for a one-pot synthesis of the 11H-indolo [3,2-c] quinoline scaffold by exploiting the formed amino indole for a subsequent Pictet-Spengler reaction with aldehydes. The photophysical properties of the carbazoles indicated good violet-blue emission with quantum yields up to 40 %.